Methodical approaches of estimation of probiotics` quality and rational principles of their usage in clinical practice - Lazarenko, Liudmyla; Bubnov, Rostyslav; Babenko, Lidiia; Melnykova, Oleksandra; Spivak, Mykola (ScienceRise: Biological Science, 2020)
Recently probiotics have been started to be commonly used as a subsidiary therapy during many illnesses, such as intestinal and urogenital infections, diseases of the gastrointestinal and respiratory tract, also joints and connective tissue lesions, some cancers, allergies, dermatological and dental diseases. However, there are still no summary guidelines for selection and estimation of probiotic strains for different clinical cases. Thus, we have made a general conclusion of estimation of probiotics` quality and development of rational principles of probiotic therapy usage in clinical practice during the treatment of patients with the most common diseases and for their prevention. There are described key principles of implementation of step-by-step estimation of probiotic culture quality in foodstuff according to regulations of World Health Organization, European Union, Ukraine and other countries. The requirements are presented for the evaluation of safety of probiotic cultures, which include testing of their in vitro and in vivo activity in different experimental models, as well as a study of their therapeutic efficacy in clinical practice in the treatment of patients and in long periods after probiotic therapy. Also there are some evidences of possible side effects, risks or low efficiency that depends on individual characteristics of the gut microbiota quantitative and qualitative composition of each patient and stage, heaviness of clinical course of each specific disease. That`s why it is very important to take all circumstances of patients` status into account and collect all previous stored knowledge of probiotics` usage